Depiction of Women as Unfair Creatures in John Donne’s “Go and Catch a Falling Star”: Utilizing Norman Fairclough’s Model as a Research Tool in the Critical Discourse Analysis - Malik Umer Ajmal; Tayyaba Zainab (Journal of Applied Linguistics, 2024)
This research paper aims to study Norman Fairclough's three-dimensional model for a critical discourse analysis of John Donne's poem "Go and Catch a Falling Star." Rooted in Critical Discourse Analysis (CDA) and building upon Fairclough's critique of Critical Linguistics, the study explores the hidden ideologies and societal attitudes embedded in the text. The poem, published in 1633, presents a satirical examination of women's perceived infidelity, and Fairclough's model serves as a tool to unravel the complexities of its linguistic features, discursive practices, and socio-cultural implications. The analysis reveals anti-feministic undertones within the broader context, where societal norms and power dynamics played a crucial role in shaping discourse. By examining the poem through the three dimensions of Fairclough's model—text, discursive practice, and sociocultural practice—the research contributes to a deep understanding of how language choices perpetuate certain perceptions of women and contribute to broader societal narratives during this historical period. Keywords: Critical  Discourse Analysis, Norman Fairclough’s Model, Go and Catch a Falling Star